The Contributions of the Mawālī to Hadith Scholarship - Raharusun, Agus Suyadi; Abdurrohman, Irwan; Abdul Kodir, Aceng (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Islamic scholarship is built by various communities. As a religion that carries the spirit of liberation, Islam provides opportunities for anyone to self-actualize. Mawālī was an element of the early Muslim community that contributed positively to hadith scholarship. During the Umayyah Dynasty, the mawālī became a second-class community, but it had a positive impact on the mawālī to take another path to be considered the main community. This research uses a qualitative method with an analytical-descriptive approach. The author used a biographical dictionary of hadith narrators to find the research data. For the data found to be informative, the author uses a historical perspective to find out the traces of his scholarship. In addition, the author confirms the hadith books. Based on the elaboration, it can be concluded that the mawālī, with its various types, contributed greatly to Islamic scholarship, especially in the field of hadith studies, from the time of the Companions to the later generations.